A Healthcare Improvement Intervention Combining Nucleic Acid Microarray Testing With Direct Physician Response for Management of Staphylococcus aureus Bacteremia - Eby, Joshua C; Richey, Morgan M; Platts-Mills, James A; Mathers, Amy J; Novicoff, Wendy M; Cox, Heather L (Clinical infectious diseases, 2018)
Nucleic acid microarray (NAM) testing for detection of Staphylococcus aureus bacteremia (SAB) and S. aureus resistance gene determinants can reduce time to targeted antibiotic administration. Evidence-based management of SAB includes bedside infectious diseases (ID) consultation. As a healthcare improvement initiative at our institution, with the goal of improving management and outcomes for subjects with SAB, we implemented NAM with a process for responding to positive NAM results by directly triggered, mandatory ID consultation. Preintervention, SAB was identified by traditional culture and results passively directed to antibiotic stewardship program (ASP) pharmacists. Postintervention, SAB in adult inpatients was identified by Verigene Gram-Positive Blood Culture test, results paged directly to ID fellow physicians, and consultation initiated immediately. In the new process, ASP assisted with management after the initial consultation. A single-center, retrospective, pre-/postintervention analysis was performed. One hundred six preintervention and 120 postintervention subjects were assessed. Time to ID consultation after notification of a positive blood culture decreased 26.0 hours (95% confidence interval [CI], 45.1 to 7.1 hours, P < .001) postintervention compared with preintervention. Time to initiation of targeted antibiotic decreased by a mean of 21.2 hours (95% CI, 31.4 to 11.0 hours, P < .001) and time to targeted antibiotics for methicillin-sensitive S. aureus decreased by a mean of 40.7 hours (95% CI, 58.0 to 23.5 hours, P < .001). The intervention was associated with lower in-hospital (13.2% to 5.8%, P = .047) and 30-day (17.9% to 8.3%, P = .025) mortality. Compared with an ASP-directed response to traditionally detected SAB, an efficient physician response to NAM was associated with improved care and outcomes for SAB.